A Dupla habilidade obrigatória no Curso de Letras da Universidade Estadual de Goiás : implicações na formação do professor de língua - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
This study aims to problematize aspects inherent to the dual obligatory habilitation in the degree in Languages of the State University of Goiás, discussing what are their implications for the training of language teachers, with a view to the processes of teaching and learning Portuguese and English languages. The study is motivated by the need to (re) think the process of training professional language teachers, problematizing the policies of teacher training established by legal documents, considering the curricular issues inherent to the culture of teacher training in degree in Languages of dual habilitation. As a theoretical basis we have supported authors such as Almeida Filho (2004, 2009, 2010), Celani (2010), Apple (1994), Oliveira (2013, 2014, 2016) Paiva (2003, 2004, 2005), Quadros-Zamboni ), among others, in addition to legislation such as the Law of Guidelines and Bases (1996), Curriculum Guidelines for Degree in Languages (2001, 2002), National Curricular Guidelines for the training of Basic Education Teachers (2002), and other policies and legislation courses at the national, state and institutional levels. To this end, a qualitative case study, also supported by a documentary study, was conducted with the trainee groups of 2017 from the UEG campuses that offer the degree in Languages, and specifically at São Miguel do Araguaia Campus. During the studies, we noticed that the dual habilitation modality promotes some (in)viabilities in the process of training language teachers and wich require critical reflection on the part of the bodies responsible for the elaboration of training policies, so that this training process to be perfected. It isn’t to apologize the teaching of one language to the detriment of the other, but to investigate in more depth how this obligatory dual capacility has reflected in the training of the teacher for the teaching of Portuguese and English language, since officially he becomes qualified to teach both disciplines.
Keywords: Curso de Letras - Universidade Estadual de Goiás; Inviavilidade da dupla habilitação; Formação docente; Professores de língua; Degree in Languages - Station University of Goiás; Inviabilities of dual habilitation; Teacher training; Teachers of language; CIENCIAS HUMANAS::EDUCACAO